Does Systematic Preliminar Colour Doppler Study Reduce Kidney Biopsy Complication Incidence? - Granata, Antonio (SAGE-Hindawi Access to Research, 2011)
While ultrasonography is widely performed prior to biopsy, colour Doppler examination is often used only to discover post-biopsy complications. Aim of this paper was to evaluate the usefulness of colour Doppler examination in planning the optimal site of puncture for renal biopsy. Present analysis includes 561 consecutive percutaneous renal biopsies performed from the same operator. Until August 2000 332 biopsies were performed after a preliminary ultrasonography (Group A). From September 2000, 229 patients underwent even a preliminary colour Doppler study (Group B). Postbioptic bleeding were categorized as minor (gross hematuria or subcapsular perinephric hematoma < 4 cmq of greater diameter) or major (hematoma >4 cmq of greater diameter; requiring blood transfusion or invasive procedures; leading to acute renal failure, urine tract obstruction, septicaemia, or death). Major complications were seen in 2.1% in Group A while in Group B only one case was reported (0.43%). Minor clinically significant complications occur in 7.8% in Group A and in 3.4% of cases of Group B. Colour Doppler reduced drastically the incidence of complications observed before the introduction of routine colour Doppler examination prior to biopsy. In our opinion, these data support the use of preliminary colour Doppler study when a biopsy is planned.